Problematic internet use and cannabis consumption: A scoping review - Kellie-Anne Bélisle; Anne-Marie Auger; Catherine Hudon; Isabelle Dufour; Roni Deli Houssein; Rasoamiadana Volanirina Rasolofomamonjy; Magaly Brodeur (Preventive Medicine Reports)
Objectives: As a growing body of research has linked cannabis consumption and problematic Internet use (PIU), more insight is needed to interpret this association. This scoping review aims to summarize the available literature on PIU and cannabis consumption and to underlie future avenues of research. Methods: We conducted an electronic search including all papers published from database inception until May 2023, using keywords related to PIU and cannabis use in the following databases: Academic Search Complete, APA PsychInfo, PubMed, SocINDEX, MEDLINE, CINAHL, and Psychology and Behavioral Sciences Collection. Studies eligible for this review had to meet the following criteria: (1) the primary theme had to be related to both PIU and cannabis consumption, (2) articles were published in a peer-reviewed journal, (3) articles were available in English or French, and (4) articles were not systematic reviews. Results: After screening 12,165 articles, 48 articles were retained for full-text reading and seven articles were included in this review. Conclusion: The available articles reveal a potential association between cannabis use and PIU, though operationalization heterogeneity challenges a conclusive interpretation of the results. Further research with improved measurement consistency is required to draw more robust conclusions.